2013
DOI: 10.1007/s12015-013-9433-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells as a Treatment for Peripheral Arterial Disease: Current Status and Potential Impact of Type II Diabetes on Their Therapeutic Efficacy

Abstract: Mesenchymal stem cells (MSCs), due to their paracrine, transdifferentiation, and immunosuppressive effects, hold great promise as a therapy for peripheral arterial disease. Diabetes is an important risk factor for peripheral arterial disease; however, little is known of how type II diabetes affects the therapeutic function of MSCs. This review summarizes the current status of preclinical and clinical studies that have been performed to determine the efficacy of MSCs in the treatment of peripheral arterial dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 86 publications
(86 reference statements)
1
45
0
Order By: Relevance
“…124 Preclinical findings showed that bone marrow–derived mesenchymal stem cells (BM-MSCs) injected into ischemic hind limbs of rats led to greater perfusion and capillary density increase than BM-MNC administration. A randomized controlled trial comparing BM-MSCs to BM-MNCs was conducted on 41 CLI patients with diabetes mellitus and demonstrated significantly improved pain-free walking time in both groups at 6 months.…”
Section: Trials Of Cell-based Therapiesmentioning
confidence: 99%
“…124 Preclinical findings showed that bone marrow–derived mesenchymal stem cells (BM-MSCs) injected into ischemic hind limbs of rats led to greater perfusion and capillary density increase than BM-MNC administration. A randomized controlled trial comparing BM-MSCs to BM-MNCs was conducted on 41 CLI patients with diabetes mellitus and demonstrated significantly improved pain-free walking time in both groups at 6 months.…”
Section: Trials Of Cell-based Therapiesmentioning
confidence: 99%
“…These include bone marrow and peripheral blood mononuclear cells [11][12][13][14][15][16][17], mesenchymal stem cells (MSCs) [18][19][20][21][22], cell lines selected based on the presence of specific markers [15,[23][24][25], adipose tissue-derived cells [26][27][28][29], and induced pluripotent stem cells-derived cells [30,31]. Each of these cell types has shown promise for the treatment of CLI in mechanistic and preclinical studies.…”
Section: Introductionsmentioning
confidence: 99%
“…In animal experiments of MSC transplantation for treating hyperglycemia and diabetes-related complications, it is indicated that paracrine and anti-inflammatory effects of MSCs are the primary mechanisms of action (19)(20)(21)(22) rather than direct engraftment and differentiation into insulin-producing cells (23,24).…”
mentioning
confidence: 99%